Penerapan Model Pembelajaran Inside-Outside Circle untuk Meningkatkan Aktivitas Belajar Siswa pada Mata Pelajaran PKn - Timour Ambarita (Universitas Negeri Medan, 2017)
The purpose of this research are: (1) To increase student learning activity on Civic subject by using Inside-Outside Circle model. (2) To improve learning outcomes by using Inside-Outside Circle technique. This type of research is classroom action research (CAR). Implementation carried out as much as 2 cycles, each cycle consists of planning, action, observation, and reflection. The subjects of the study were the fourth grade students of SDN 101768 Tembung. Data collection techniques used were interviews, observations and tests. The results show that the use of Inside-Outside Circle model can increase student activity and learning result which is seen from the increase of active participation of students in group discussion, ability to identify learning with Inside-Outside Circle model. Improved learning process is able to increase student learning activities. The liveliness of students in asking before action 14,81%, in cycle I is 37,2%, in cycle II is 81,45%. The activity of students in answering questions before action 7.4%, in the first cycle is 37.03%, the second cycle is 74.07%. Student activity in attitude before action of 7,4%, in cycle I is 44,4%, in cycle II is 74,07%. Activity of student in doing problem independently before action 37,03%, in cycle I is 55,5%, in cycle II is 74,07%. Value of PKN student learning outcomes before action is only 31.25% with an average score of 56.5 while in cycle I, the value of student learning outcomes increased to 62.5% with a mean score of 70.31. In the second cycle the value of student learning outcomes that reach KKM is 81.25% with an average value of 74.06.